2020
DOI: 10.1002/1878-0261.12785
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic–smoking interaction reveals histologically heterogeneous effects of TRIM27 DNA methylation on overall survival among early‐stage NSCLC patients

Abstract: Tripartite motif containing 27 (TRIM27) is highly expressed in lung cancer, including non-small-cell lung cancer (NSCLC). Here, we profiled DNA methylation of lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) tumours from 613 early-stage NSCLC patients and evaluated associations between CpG methylation of TRIM27 and overall survival. Significant CpG probes were confirmed in 617 samples from The Cancer Genome Atlas. The methylation of the CpG probe cg05293407 TRIM27 was significantly associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…1,2 At present, there are no clear results for the cause of NSCLC in clinical practice, but it is known that environment, heredity, and bad living habits are high risk factors that cause this disease. 3,4 Radiotherapy is one of the local treatments for NSCLC, but the emergence of radioresistance greatly reduces the probability of successful radiotherapy. 5,6 Therefore, seeking effective targets to improve radiosensitivity is expected to offer a theoretical basis for improving the cure rate of NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 At present, there are no clear results for the cause of NSCLC in clinical practice, but it is known that environment, heredity, and bad living habits are high risk factors that cause this disease. 3,4 Radiotherapy is one of the local treatments for NSCLC, but the emergence of radioresistance greatly reduces the probability of successful radiotherapy. 5,6 Therefore, seeking effective targets to improve radiosensitivity is expected to offer a theoretical basis for improving the cure rate of NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking is one of the leading risk factors to lung cancer morbidity and mortality [20,21]. Our previous study found that a two‐way interaction between cg05293407 TRIM27 and smoking reveals the histologically heterogeneous effect of TRIM27 DNA methylation on survival among early‐stage NSCLC patients [22].…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, gene–gene and gene–environment interactions provide important clues regarding biologic mechanisms of complex diseases [23] and are associated with the overall survival of NSCLC [10,11,14,22,24]. However, tumorigenesis and progression of complex diseases, such as NSCLC, often involves a multistep, multigenic, and multicausal biological process [25]; interactions between two relevant factors may only provide limited information understanding the cancer process driven by multiple factors [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hsa_circ_0006168 (circ_0006168) is derived from CCR4-NOT transcription complex subunit 6 like (CNOT6L) gene and located at chr4:78,694,234–78,697,546, and it has been reported to act as an oncogene in ESCC [ 16 ]. Moreover, hsa_circ_0030998 suppressed lung cancer tumorigenesis and Taxol resistance by sponging miR‐558 [ 17 ]. In addition, hsa_circ_0002483 inhibited the progression and enhanced the Taxol sensitivity of non-small cell lung cancer via regulating miR-182-5p [ 18 ].…”
Section: Introductionmentioning
confidence: 99%